Effects of intrabronchial foreign body retention - YILDIZELİ, BEDRETTİN (WILEY-LISS, 2002)
Unrecognized bronchial foreign bodies (Fbs) cause irreversible changes in the airways. However, Vie exact course of these changes is not well-known. We developed an animal model of bronchial obstruction to radiologically and histopathologically assess the development of postobstructive pulmonary changes. A piece of peanut was placed in the airways of 21 rabbits through a 2.5-mm rigid bronchoscope. Animals were divided into three groups (groups I-III) that were sacrificed on day 3,10, and 30 after Fb placement, respectively. Prior to sacrifice, since there were no differences between the groups prior to Fb placement, computerized tomography (CT) of the lung was taken, and the lungs were harvested for histologic analysis under light microscope. In group 1, leukocyte infiltration around the bronchial wall (P = 0.0003) and edema (P = 0.0384) around the alveolar septa were the predominant histological findings. The CT scan was normal. In group 11 and group 111, increased amounts of mononuclear cells and macrophage infiltration around the bronchial wall were observed (P = 0.0008, P = 0.0409, respectively). There were no differences in presence of granuloma formation, emphysema, atelectasis, or thickness of alveolar septa among the three groups. The CT scan of group If showed consolidations plus minimal bronchial dilatation in the involved lung of the rabbits (P not significant). Bronchial cartilage destruction was seen in 4 out of 7 rabbits in group III (P = 0.0071). We conclude that 30-day retention of intrabronchial peanut caused bronchial cartilage destruction and fibrosis that were attributed as bronchiectatic changes in the airways of the lung parenchyma. Therefore, any case with suspected foreign body aspiration should be treated immediately to prevent possible irreversible changes of the lungs. Pediatr Pulmonol. 2002; 33:362-367. (C) 2002 Wiley-Liss, Inc.
Keywords: foreign body; lung; animal model; bronchiectasis; inflammation; radiology; complication; CT scan; histology; BRONCHIECTASIS; ASPIRATION; CHILDREN; DIAGNOSIS; SYMPTOMS; REMOVAL; BODIES